LOGICAL MATHEMATICAL INTELLIGENCE TOWARD STUDENTS PARTICIPATION AND CHARACTER BUILDING IN INDONESIA - Sri Handayani (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2017)
In Indonesia, participation in English Language Teaching ( ELT) profoundlychallenging for the students. This research is directed to find the students participation inclassroom, specifically in foreign language class and its support. This research is case studytoward the teaching learning process in teaching learning process especially in Vocabularyclass. The subject of this research is the students who are taking Vocabulary class inteaching English Language Teaching. Meanwhile interview, questionaer and observationare applied to gain the data. Those techniques are directed to gain the data for studentsparticipation. The interview were done toward students during classroom and also afterclasstime. Observation was conducted directly in teaching learning process, and in the endof the class they are given questionaer to be fullfilled. The triangulation method were doneto ensure the validity of the data. The researcher used different sources and also tecniquesto maintain the valid data. After the data were accurately collected, they were then analyzedusing descriptive qualitative research. The result of the research shows that there are twokinds of activities dominating the participation of students, they were taking into accountwhile lecturer explaining material (75%) and asking about matter learning which haven’tbeen understood (65%). Integrating logical mathematical intelligence in EFL class provelyincrease students participation as well as enhance students character. This researchconstribute to the development of applying innovative strategies and approaches in Englishlanguage teaching in Indonesian since it growth as fast the demand in society life.Key words: English Language Teaching, logical mathematical intelligence,participation, character, case study